Contribution Of Formal And Non-Formal Islamic Religious Education In Improving The Quality Of Morals Of Khalisaturrahmi Smp It School Students In Binjai City - Abdi Sumarna; Chairani Chairani; Widya Aprillia (AR-RASYID : Jurnal Pendidikan Agama Islam, 2023)
This article discusses the role of formal and non-formal Islamic religious education in improving akhlakul karimah. There are still students or students whose morals are not good, especially the manners towards teachers researchers want to improve good morals towards teachers in order to get useful knowledge and blessings. This study used descriptive qualitative using data analysis techniques in the form of observation and interviews where the researchers took observations at SMP IT Khalisaturrahmi Binjai where researchers took qualitative primary data sources obtained from Islamic Religious Education teachers. In this study, the sources of secondary data are theses, theses and articles relating to the research being conducted. The first research is that a students must obey the teacher with habituation when the teacher drives a motorbike or car or is walking, the students bow their heads while giving a smile. Work program makes a moral debriefing work program once a week aimed at having good morals towards fellow students, teachers, parents and even within the community. To produce results such as when in class students or students must first enter the class to welcome the teacher who will enter. The second is the teacher's guidance for students, namely using the method of concrete stories such as giving alms and we also have to be sincere and that must also be set as an example by the teacher, so that from that method students who previously behaved badly become good so that it can be applied in the community. Third, if there are students who are difficult to control, namely by approaching giving advice and motivation so that a student has good morals, without denying that a stubborn student can occur due to internal factors such as lack of love for parents, then it would be nice for the teacher to talk to four students. Alhamdulillah, in this way students can change from bad morals to good ones.